1995
DOI: 10.1021/j100020a063
|View full text |Cite
|
Sign up to set email alerts
|

H2 and CO Electrooxidation on Well-Characterized Pt, Ru, and Pt-Ru. 1. Rotating Disk Electrode Studies of the Pure Gases Including Temperature Effects

Abstract: The electrooxidation of pure hydrogen and carbon monoxide on Pt-Ru alloy surfaces was studied as a prelude to a companion study (Part 2) of the electrooxidation of CO/H* mixtures such as those produced by steam reforming of hydrocarbon fuels. The rotating disk electrode (RDE) technique was uniquely combined with characterization of the electrode surface composition in UHV by low-energy ion-scattering spectrosocopy (LEIS). Whereas hydrogen oxidation was found to be a very fast reaction on both pure Pt and Pt-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
448
1
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 535 publications
(511 citation statements)
references
References 15 publications
42
448
1
4
Order By: Relevance
“…This composition range exhibits superior performance compared to others in this binary composition spread. These results are consistent with prior work involving the sampling of discrete 10 or array-type 28 Pt-Ru catalysts for hydrogen oxidation. Although Figure 4b indicates that CO oxidation commences at the lowest potentials for Ru compositions near 80%, this is a less desirable composition because of the low activity for hydrogen oxidation.…”
Section: Scheme 1 Schematic Of Gradient Fabrication Bysupporting
confidence: 90%
See 1 more Smart Citation
“…This composition range exhibits superior performance compared to others in this binary composition spread. These results are consistent with prior work involving the sampling of discrete 10 or array-type 28 Pt-Ru catalysts for hydrogen oxidation. Although Figure 4b indicates that CO oxidation commences at the lowest potentials for Ru compositions near 80%, this is a less desirable composition because of the low activity for hydrogen oxidation.…”
Section: Scheme 1 Schematic Of Gradient Fabrication Bysupporting
confidence: 90%
“…These observations are consistent with the high activity of Pt and the low activity of Ru for hydrogen oxidation. 10,28 In addition, the formation of ruthenium oxides …”
Section: Scheme 1 Schematic Of Gradient Fabrication Bymentioning
confidence: 99%
“…The shift of the CO oxidation toward higher potentials due to the rotation of the electrode is a consequence of the negative reaction order of CO oxidation on a platinum surface. 27,28 Thus, rotating the electrode during the CV in CO purged electrolyte can help to separate the potential range of CO oxidation from the potential range of hydrogen underpotential deposition. This separation is a prerequisite for the applicability of the CO-baseline method for H upd analysis.…”
Section: H123mentioning
confidence: 99%
“…An advantage of this measurement is its ability of simulating the continuous flow conditions encountered in the real operation of PEMFC. 19,20 Figure 5 shows the potentiodynamic oxidation of 0.1% CO/H 2 on Pt/ C and Pt 4 Mo 1 /C alloy catalyst in 1 M H 2 SO 4 at 60 o C. In order to assure the equilibrium of CO adsorption, CO was adsorbed at 0.1 V for 3 minutes prior to recording the oxidation current. The magnitude of the oxidation current with Pt 4 Mo 1 /C catalyst in the low potential region was much greater than that with Pt/C.…”
Section: Resultsmentioning
confidence: 99%
“…4,6 Typically, transition metals such as ruthenium, tin, tungsten, or molybdenum have been utilized as a component of the alloys, [7][8][9][10][11][12][13][14][15][16][17][18] and among them ruthenium (Ru) has received great attention due to the significant improvement in the anodic oxidation of CO with PtRu catalyst. 7,[19][20][21][22] Watanabe and coworkers proposed a bifunctional mechanism to explain such enhancement of catalytic activity, where Ru promotes the adsorption of active oxygen species which plays a critical role in the electro-oxidation of CO. 21 Along with Ru, molybdenum (Mo) has attracted scientists' interest because of their relatively lower cost as well as the catalytic activity of PtMo comparable to that of PtRu. Grgur and coworkers reported that the magnitude of H 2 oxidation current with the PtMo catalyst in low-overpotential region is nearly the same as that observed with the PtRu catalyst.…”
Section: Introductionmentioning
confidence: 99%